COLLAPSE OF THE TRADITIONAL AGRICULTURAL CIVILIZATION IN THE MOUNTAINOUS DAGESTAN AND POSSIBLE WAYS TO OVERCOME THE CRISIS - Z. M. Asadulaev; A. M. Musaev (Юг России: экология, развитие)
The aim is to analyze the current state of mountain agriculture in a crisis of traditional agricultural civilization based on terraced agriculture.Results and discussion. The introduction defines the concept of "innovation development" and the necessity of the institutional approach to identify and break the obstacles for the development of the agricultural sector in mountainous Dagestan. The following section provides a summary of the history of agricultural civilization in the mountainous Dagestan and proves the necessity of the inventory of resources before the adoption of the program of development of this region. Then, consecutively, it discusses the need for an inventory of land resources, vegetation resources (including genetic resources) and wildlife resources. Each section provides consistent guidance on inventory and further utilization of the resource. We discuss some of the conceptual approaches to the improvement of the agricultural sector, in particular branding the territory, promotion of horticulture areas in mid and high lands with new crops, the possibility of medicinal crop on terraced land.Conclusions. The findings discuss the impact of the humanitarian factor on the effectiveness of the implementation of innovative approaches for the development of the agricultural sector in the mountainous Dagestan.